Biological Analysis of Factors Influencing the Acceleration of Menopause Age in Indonesian Women - Nursitiyaroh; Rosfika Sari; Dian Martiani; Erta Jayanti; Rahma; Ririn Aryanti; Siti Nurdianah; Desi Komalasari; Diah Mustika Rini; Emi Liawati; Irna Widayati; Sustini Megawati (Postgraduate, University of Mataram, 2024)
Menopause marks the end of a woman's menstrual cycle, typically around age 51 in Indonesia. Early menopause, before age 45, increases the risk of cardiovascular disease, osteoporosis, and mental health issues. This study examined factors affecting menopause age, including BMI, excess weight, menstrual disorders, genetics, collagen supplement use, diabetes history, parity, hormonal contraception, age at menarche, fast food consumption, and nutritional status. Data from 1683 menopausal women were collected through questionnaires, BMI calculations, and analyzed using chi-square tests with SPSS 25. Results showed no significant influence of BMI, excess weight, genetics, collagen supplements, diabetes, fast food, or nutritional status on menopause age (p > 0.05). However, parity, hormonal contraception, age at menarche, and menstrual disorders significantly influenced menopause timing (p < 0.05). These findings offer insights for improving women’s reproductive health and guiding preventive measures.